2022
DOI: 10.1021/acs.inorgchem.2c01019
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive Anthracene-9,10-dicarboxylic Acid for Tuning of Photochromism in the Cd/Zn Coordination Polymers

Abstract: Electron transfer photochromic materials with photo-triggered radicals have received huge interest from chemists due to their potentialities in anticounterfeiting, displays, energy conversion, and information storage. However, utilizing the sole carboxylic acid to synthesize novel electron transfer photochromic species is still confronted with huge challenges. Herein, an acentric three-dimensional network Cd2(ADC)2(DMF)2(H2O) (1; ADC = anthracene-9,10-dicarboxylate; DMF = N,N-dimethylformamide) and a two-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The Cd-O bond length is in the range of 2.201(4)-2.472(4) Å (Table S2 †), which corresponds to those of the reported Cd(II)based coordination polymers. 33,34 Owing to the existence of long Hbpdc + pendants, 2D sheets in compound 1 interdigitate with its neighbouring counterparts to form a 3D supramolecular structure (Fig. 2) with the assistance of C-H⋯O and O-H⋯O hydrogen bonding interactions.…”
mentioning
confidence: 99%
“…The Cd-O bond length is in the range of 2.201(4)-2.472(4) Å (Table S2 †), which corresponds to those of the reported Cd(II)based coordination polymers. 33,34 Owing to the existence of long Hbpdc + pendants, 2D sheets in compound 1 interdigitate with its neighbouring counterparts to form a 3D supramolecular structure (Fig. 2) with the assistance of C-H⋯O and O-H⋯O hydrogen bonding interactions.…”
mentioning
confidence: 99%
“…As a result, the coordination assembly strategy provides more efficient electron transfer pathways and promotes photochromic behavior. The effect of coordination of photochromic ligands with metal ions on the electron transfer photochromism has been reported in other works. ,, …”
Section: Resultsmentioning
confidence: 58%
“…To better compare the coloration rates of the four compounds, we measured the photochromic kinetics of these compounds at 500 nm of the UV–vis spectra by the kinetic rate equation of ln­( A 0 – A ∞ )/( A t – A ∞ ) = Kt , where A 0 , A t , and A ∞ represent the absorbance that was observed at the beginning, versus time and the end of the reaction, respectively. The linear fitting curves were performed, and the results showed that the coloration efficiency followed the first-order reaction kinetics. As shown in Figure , compound 2 shows the fastest color rendering rate. To investigate the differences in the rate of discoloration, we analyzed the structure of the compounds and found that the four complexes exhibited the same number of intermolecular/intramolecular hydrogen bonds, while compound 2 showed the shortest distance in the intramolecular hydrogen bonds, with the C17–H17···O3 distance of 2.8185(2) Å, whereas the other compounds are C34–H34···O5 of 2.8322(1) Å for 1 , C43–H43···O6 of 2.8365(1) Å for 3 , and C42–H42···O5 of 2.8238(2) Å for 4 (Tables S10–S13), respectively.…”
Section: Resultsmentioning
confidence: 98%
“…[18][19][20][21] Especially, the photochromic performances in terms of photoresponsive rate, photo-response range and coloration contrast of these hybrids have been optimized by rational selection and masterly integration of EDs and EAs as well as effectively modulating intermolecular electronic behaviors. [22][23][24][25][26][27][28][29][30][31] Intermolecular charge transfer (ICT) and photoinduced intermolecular electron transfer (PIET) are two fundamental electron behaviors, and both interactions exist between EDs and EAs in electron donor-acceptor hybrid systems. ICT is the continuous charge transition and recombination between EDs and EAs, and is related to the initial color states of these hybrids because of their noncharacteristic absorption in the visible light region generally.…”
Section: Introductionmentioning
confidence: 99%
“…18–21 Especially, the photochromic performances in terms of photo-responsive rate, photo-response range and coloration contrast of these hybrids have been optimized by rational selection and masterly integration of EDs and EAs as well as effectively modulating intermolecular electronic behaviors. 22–31…”
Section: Introductionmentioning
confidence: 99%